The relationship between State-Trait Anxiety and intelligent in Puerto Rican psychiatric patients - Martinez-Urrutia, Angel; Spielberger, Charles D. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Psychiatric patients at the San Juan Veterans Administration Hospital were given the Spanish version of che WAIS, the Escala de Inteligencia Wechsler para Adultos (EIWA), and the Spanish edition of Spielberger’s State-Trait Anxiety Inventory (STAI). The STAI A-State scale was administered immediately before the EIWA (A-State-i), and, again, immediately after the EIWA (A-State-2). A short form of the STAI A-State scale was also given immediately after each of the eleven EIWA subtests. Significant negative correlations of the STAI A-Trait scale and the A-State-2 scale were obtained with the EIWA Full Scale, the Verbal and Performance scales, the “Wechsler Triad,” and the Timed and Untimed EIWA subtests. In addition, scores on each EIWA subtest were inversely correlated with the Short Form A-State scales, except for Vocabulary and Analogies. Patients with high A-Trait scores showed higher levels of A-State intensity while performing on the EIWA than low A-Trait patients. Moreover, the A-State levels of the HA-Trait patients tended to increase during their performance on the EIWA, while level of A-State for the LA-Trait patients remained relatively constant from the beginning to die end of the EIWA.